At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
0
Step-by-step explanation:
Let's solve your equation step-by-step.
[tex]4b+6=2-b+4[/tex]
Step 1: Simplify both sides of the equation.
[tex]4b+6=2-b+4[/tex]
[tex]4b+6=2+-b+4[/tex]
[tex]4b+6=(-b)+(2+4)[/tex](Combine Like Terms)
[tex]4b+6=-b+6[/tex]
[tex]4b+6=-b+6[/tex]
Step 2: Add b to both sides.
[tex]4b(+b)+6=-b(+b)+6[/tex]
[tex]5b+6=6[/tex]
Step 3: Subtract 6 from both sides.
[tex]5b+6(−6)=6(−6)[/tex]
[tex]5b=0[/tex]
Step 4: Divide both sides by 5.
[tex]\frac{5b}{5} =\frac{0}{5}[/tex]
[tex]b=0[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.